Active methodologies and subjective construction of learning in Chilean psychology students: a case study from a historical-cultural perspective - Guerra Díaz, Felipe (2026)
The purpose of the study was to analyze the subjective configurations of psychology students regarding the development of active methodologies for addressing psychosocial issues. In particular, it focuses on the Problem-Based Learning and Service-Learning strategies developed in the training process of 68 students at a university in northern Chile. To carry this out, a qualitative epistemology and a constructive-interpretive paradigm were adopted, using field diaries, discussion groups, and interviews as data collection techniques. The findings show initial subjective configurations in students, marked by uncertainty and tension, which gradually develop into confidence, where contexts create tension and mobilize them in the search for solutions. At the end of the process, they are able to recognize the importance of collaboration, validating and attributing value to different types of knowledge. In the case of teaching staff, they move from a directive logic to a mediating role in the teaching-learning process. Finally, in accordance with the above, it is concluded and recommended that these active methodologies be implemented in real contexts from the initial stages of the training process, as they promote student autonomy, reduce the demand on the teacher, incorporate theoretical aspects, and strengthen the link with communities. In addition, they allow for the construction of realistic and contextualized professional competencies and identity.